Photochemical source of metals for sediments - Kopácek, Jirí; Maresová, Marie; Norton, Stephen A; Porcal, Petr; Veselý, Josef (Environmental science & technology, 2006)
A mass budget study of major in-lake Al fluxes, palaeolimnological data on a >10,000 year old sediment record, and in situ photochemical experiments performed at Plesné Lake (Czech Republic) suggest that photochemical liberation of organically bound aluminum (Al) and iron (Fe) by solar radiation is a significant natural source of their ionic species for lakes and subsequent oxyhydroxides for sediments. The results show that photochemically induced transformation of dissolved Al and Fe to solid oxyhydroxides deposited to Plesné Lake sediment dominated (91 and 73%, respectively) their sedimentary flux throughout the preindustrial era, since soil formation initiated in the catchment. The following sequence of processes occurs: (i) soil organic acids dissolve and bind metals and export them from terrestrial to aquatic systems. (ii) Photochemical decomposition of organic-metal complexes liberates a significant portion (approximately 50% in Pleseé Lake) of organically bound Al and Fe as inorganic ions. (iii) The liberated ionic Al and Fe hydrolyze, precipitate as oxyhydroxide particles, and settle. We hypothesise that the same Al and Fe transporting process occurs in other lakes and coastal marine areas and is ecologically important because Al and Fe oxyhydroxides can bind trace metals and phosphorus.
Keywords: Metals; Carbon; geologické sedimenty; Geologic Sediments; kovy; Photochemistry; fotochemie; uhlík